1996
DOI: 10.1002/(sici)1096-9098(199612)63:4<221::aid-jso2>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Calcification in colorectal hepatic metastases correlates with longer survival

Abstract: Background Calcification occurs in 12–27% of hepatic colorectal metastases, but its clinical significance and its influence on prognosis are unknown. Methods All patients diagnosed with colorectal liver metastases at the Ottawa Regional Cancer Centre in 1991 (n = 97), as well as those enrolled in chemotherapy trials in 1990–1992 (n = 51), were entered into a retrospective cohort study. Thirty‐six patients were excluded due to inadequate follow‐up. In the remaining 112, abdominal CT scans and/or ultrasound exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…The exact mechanism of extraosseous uptake of 99m Tc-MDP in breast, lung, and colorectal cancer is that adenocarcinoma and its metastases possess a mucinous component that may calcify because of internal tumour glycoprotein that binds calcium [14, 15, 17]. In addition, studies reported that calcification in colorectal liver metastasis is generally considered a good indicator of the response to treatment [18]. Therefore, WBS and SPECT/CT may be a potentially useful imaging modality to evaluate responses to treatment for patients with colorectal liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism of extraosseous uptake of 99m Tc-MDP in breast, lung, and colorectal cancer is that adenocarcinoma and its metastases possess a mucinous component that may calcify because of internal tumour glycoprotein that binds calcium [14, 15, 17]. In addition, studies reported that calcification in colorectal liver metastasis is generally considered a good indicator of the response to treatment [18]. Therefore, WBS and SPECT/CT may be a potentially useful imaging modality to evaluate responses to treatment for patients with colorectal liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…There are exceptional situations where psammoma body formation is a feature of cholangiocarcinoma (Yamada et al 2000). Secondary calcification is well known in carcinoma metastases, in particular colorectal carcinoma (CRC) metastases (Miele and Edmonds 1963;Green and Stephens 1971;Kutzner and Wagner 1973;Sanchez Perez et al 1995;Easson et al 1996). Calcified hepatic metastases may be the first manifestation of CRC (Sanchez Perez et al 1995), and they have characteristic CT features.…”
Section: Calcified Tumors In the Livermentioning
confidence: 99%
“…Among 265 patients with hepatic CRC metastases, 11 % had calcified metastases at presentation and 4 % developed calcification during chemotherapy (Hale et al 1998). Calcification in colorectal hepatic metastases has been found to correlate with longer patient survival (Easson et al 1996). Calcifications are also rather typical for certain vascular tumors.…”
Section: Calcified Tumors In the Livermentioning
confidence: 99%
“…Imaging, particularly helical computed tomography (CT) scan, is used to assess the response to treatment. Chemotherapy can result in images showing shrinkage, disappearance or calcification of liver metastases; these signs are generally good indicators of the response to treatment [1]. Liver metastases, especially in mucin-producing adenocarcinoma, may occasionally contain a few calcifications prior to therapy.…”
Section: Introductionmentioning
confidence: 99%